KOHESI PADA TEKS CERITA RUBRIK ANAK-ANAK, REMAJA, DAN DEWASA DALAM MAJALAH PANJEBAR SEMANGAT - Guntur Yuli Triasmoro; Sumarlam Sumarlam; Djatmika Djatmika (Center of Language and Cultural Studies, 2016)
The aim of this research is to find grammatical and lexical cohesion in Javanese magazine Panjebar Semangat included in the rubrics: Wacan Bocah, Manja, and Cerkak. The study used content analysis with qualitative approach. Data of this study were lingual units such as utterances, sentences, and clauses taken from the rubrics. Data were collected using review and note technique. Data were analyzed using “agih method”, “bagi unsur langsung” (BUL), substitution and elliptisis technique. The results shows that grammatical aspect used in Wacana Bocah, Manja, and Cekak rubric in Panjebar Semangat magazine included: reference, substitution, ellipsis, conjungtion. Lexical aspects in the disourses comprise of: repetition, synonym, antonym, collocation, hyponym, and equivalency. Theme that found in Wacan Bocah, Manja, and Cekak rubric is agriculture, education, love, friendship, life style, spirituality, law, and culture.